2000
DOI: 10.1111/j.1745-3992.2000.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Accommodation Strategies on English Language Learners' Test Performance

Abstract: How can we make effective accommodations for nonnative English speakers taking mathematics measures? What kinds of accommodations are useful and what kinds are not? Where does this research need to go in the future?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 16 publications
2
111
1
Order By: Relevance
“…Paper-based glossaries have been found to be effective for students with mid-to low-level English reading proficiency (Kiplinger et al, 2000). A caveat here is that a paperbased glossary is primarily effective only in instances where there is either ample or extended time included for the test, and it has been found that paper-based glossary use without this extra time can hinder ELs' performances Abedi, Lord, Hofstetter, & Baker, 2000). posited that because students using the paper-based glossary need to take extra time to look up a given word, this accommodation is ineffective unless test administrators provide ample time for students to use the accommodation.…”
Section: Paper-based Glossariesmentioning
confidence: 99%
“…Paper-based glossaries have been found to be effective for students with mid-to low-level English reading proficiency (Kiplinger et al, 2000). A caveat here is that a paperbased glossary is primarily effective only in instances where there is either ample or extended time included for the test, and it has been found that paper-based glossary use without this extra time can hinder ELs' performances Abedi, Lord, Hofstetter, & Baker, 2000). posited that because students using the paper-based glossary need to take extra time to look up a given word, this accommodation is ineffective unless test administrators provide ample time for students to use the accommodation.…”
Section: Paper-based Glossariesmentioning
confidence: 99%
“…According to Abedi et al (2000), language is important, in not only assessing language courses, but also content courses. They reiterated that, for instance, English is important for learning of context courses and that there was a correlation between proficiency in English and performance in Mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…According to Abedi et al (2000), a valid accommodation is one that helps the target but does not affect the scores of other students. This means it should be capable of improving the performance of students to classify ELL and LEP because of their handicap, but it should not be beneficial to the native speakers.…”
Section: Dealing With L2 Assessment Language Difficultiesmentioning
confidence: 99%
“…Other researchers (Abedi, Lord, Hofstetter, & Baker, 2000;Beth, 2016) indicated that with ELLs' anxiety lowered, they were physiologically more able to accept new challenges and grapple with new concepts and problems. Therefore, math teachers are expected to create a safe and inclusive classroom environment to lower ELL students' anxiety.…”
Section: Creating a Safe And Inclusive Classroom Environmentmentioning
confidence: 99%